Deficient flavoprotein component of the NADPH-dependent O2-.-generating oxidase in the neutrophils from three male patients with chronic granulomatous disease. - Gabig, T G (1984)
The NADPH-dependent O2-.-generating oxidase in subcellular fractions from the neutrophils of three male patients with chronic granulomatous disease was compared with the corresponding preparations from normal neutrophils. The oxidase from normal neutrophils contained flavin adenine dinucleotide in an approximately 0.9:1 molar ratio with cytochrome b559. Each of the three chronic granulomatous disease patients had decreased amounts of the flavoprotein component of the oxidase fraction. The oxidase from two chronic granulomatous disease patients had undetectable amounts of cytochrome b559 whereas the third patient had a normal content of cytochrome b559, which was spectrally indistinguishable from the normal. The intrinsic cytochrome b559 in the oxidase fraction from stimulated neutrophils of the latter chronic granulomatous disease patient was not reduced by NADPH under anaerobic conditions, in distinction with the previously reported reduction of the normal cytochrome b559 under identical conditions. We conclude that the flavoprotein component of the oxidase may mediate transfer of electrons from NADPH to the cytochrome b559 in normal neutrophils, and that deficiency of this flavoprotein is associated with the chronic granulomatous disease phenotype in the three patients studied.